Corrosion of wire arc sprayed ZnMgAl. Issue 6 (28th August 2014) - Bobzin, K.; Oete, M.; Linke, T. F.; Schulz, C.
<x xml:space="preserve">Abstract</x> In the past 10 years, hot‐dip‐galvanized ZnMgAl coatings containing 1–2 wt% of Mg and Al each and a Zn base have demonstrated their superior corrosion resistance compared to ZnAl coatings. However, applications of ZnMgAl coatings have been limited to continuous strip galvanizing so far. In this paper, a cored wire for arc spraying of ZnMgAl was developed and the resulting coating was compared to wire arc sprayed Zn and ZnAl15 coatings. The coatings were exposed to the neutral salt spray test for up to 2448 h and the corrosion products were characterized using optical microscopy, EPMA and XRD. ZnMgAl showed superior corrosion resistance compared to ZnAl15 and Zn due to the formation of layered double hydroxides (LDH) and delaying the formation of hydrozincite as a result of the formation of MgCO3.